The World Bank's Publication Record - Ravallion, Martin (Springer, 2015)
The World Bank claims to be a “knowledge bank,” but do its knowledge products influence development thinking, or is the Bank merely a proselytizer? The World Bank is a prolific publisher; for example, it has published more journal articles in economics than any university except Harvard. But what about their impact on development thinking? Using citation data from Google Scholar it is hard to discern more than a negligible impact for a great many Bank publications. However, a sizable minority of its journal articles and books have been highly cited. Compared to leading research universities and other international institutions, the Bank’s ranking in terms of widely-used citation-based indices is no lower than for its journal article counts. This suggests that the Bank’s research does much more than proselytize.